Mitral paravalvular leak 3D printing from 3D-transesophageal echocardiography - proof of concept. (4th February 2022) - Jedrzejek, M; Kozlowski, M; Pysz, P; Wojakowski, W; Smolka, G
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ministry of Science and Higher Education Background: Paravalvular leak (PVL) may occur  in almost 15% of patients undergoing surgical mitral valve replacement. This complication can cause congestive heart failure and hemolysis. Multimodal imaging including computed tomography (MSCT) and 3D-transesophageal echocardiography (3D-TEE) is essential for assessment of PVLs. 3D-TEE-based 3D-printing might be useful in preprocedural planning of PVL closure for the optimization of transcatether procedures. In contrast to 3D-printing based on MSCT, use of 3D-TEE for segmentation and printing is not standardized. Purpose: A proof of concept study to evaluate 3D printing of mitral PVLs using 3D-TEE. Methods: A case of a 64-year-old woman with 2 clinically significant PVLs around a mitral prosthetic valve is presented. In 3D-TEE (Philips Epiq) anteromedial defects were visualized (surgical view). Qlab Station was used to export the 3D recording of PVLs with surrounding tissue in cartesian DICOM format. Next Slicer, a free open-source software, was used for segmentation and preparation of a STL (stereolithography) file. The PVL model was printed with Starsys Objet 30 printer using Med620 material. Diameters PVLs were the same in 3D Echocardiography and 3D printed model (12mm and 9mm). Results: Printed PVL model and corresponding 3D-TEE image are shown in Figure 1 and Figure 2, respectively. Conclusion(s) Proof of concept study confirms feasibility of using standard 3D-TEE and open source software for preparation of 3D models of anatomically complex mitral PVLs. Further studies to assess cost-effectiveness and clinical applicability of the presented methodology are ongoing.